Pengaruh Dosis Herbisida Ethoxysulfuron 15 WG Terhadap Gulma, Pertumbuhan Dan Hasil Tanaman Padi Varietas Ciherang - Dedi Widayat; Dani Riswandi; Aty Fujiaty Setiawan (Faculty of Agriculture, Pattimura University, 2017)
Weeds in rice fields decrease the quantity and quality of yield. One of the methods used to control weeds is chemical herbicide. The objective of this research was to find out the effective dosages of herbicide Ethoxysulfuron 15 WG on weeds growth as well as growth and yield of rice plants var. Ciherang. This experiment was used Randomized Block Design with seven treatments and four replication. The Ethoxysulfuron doses trated to rice field 6 g/ha, 9 g/ha, 12 g/ha, 15 g/ha and 18 g/ha. The two control treatments were mechanical weeding, and without weeding and herbicide. The experimental result showed that Ethoxusylfuron herbicide with the dosage of 9 g/ha could suppress the growth of weed Ludwigia adscendens, Ludwigia perrenis, Fimbristylis miliacea,other weeds, and total weeds and give a good impact on yield of rice plants.